Prevalence of Behavioral Addictions and Their Relationship With Stress and Anxiety Among Medical Students in Saudi Arabia: A Cross-Sectional Study - Hakami, Alqassem Y.; Ahmad, Rami Ghazi; Alsharif, Abdullah; Ashqar, Alaa; AlHarbi, Fahad A.; Sayes, Mohammed; Bafail, Anas; Alqrni, Ali; Khan, Mohammed A. (Frontiers in Psychiatry, 2021)
Behavioral addiction is identified as any compulsive, repeated, and persistent behavior that leads to significant and functionally impairing harm or distress. The aim of this study is to determine the prevalence of internet, video-gaming, and pornography addictions among medical students in Western region. In addition, we intend to investigate the relationship between these behavioral addictions with stress and anxiety. Our study was a cross-sectional study with a sample size of 225. The study participants were medical students in their 3rd, 4th, and 5th academic years from five different medical colleges in Western region. The questionnaire included demographics and adapted five different pre-validated scales: Young’s Internet Addiction Test – Short Version (IAT-SV), Internet Gaming Disorder Scale 9 – Short Form (IGDS9-SF), (PPC scale), Perceived Stress Scale (PSS), and Generalized Anxiety Disorder 7-item scale (GAD-7). The IAT-SV scale showed: 71 (31.6%) of the participants had normal internet usage, 51 (22.7%) participants showed problematic usage, and 103 (45.8%) used the internet pathologically. The IGDS9-SF scale had observed the following values: 220 participants (97.8%) were non-disordered, and 5 participants (2.2%) were found to be disordered. This study showed high prevalence of internet addiction and low prevalence of internet gaming disorder. Also, it gave more understanding to a possible association between these behavioral addictions with stress and anxiety.